Multiple relocation cases in disaster-related deaths after the Fukushima nuclear accident - Ito, Naomi; Sawano, Toyoaki; Uchi, Yuna; Kawashima, Moe; Kitazawa, Kemmei; Moriyama, Nobuaki; Amir, Isamu; Yoshimura, Hiroki; Nonaka, Saori; Saito, Hiroaki; Ozaki, Akihiko; Yamamoto, Chika; et al. (Frontiers in Disaster and Emergency Medicine, 2024)
Introduction: Relocation after a disaster often has negative health effects on vulnerable people, particularly older adults. However, little is known about the number of repeated evacuations and relocations after disasters among those experienced disaster-related deaths. This case series aimed to summarize the secondary problems and mortality risks in patients involved in relocation after disasters. Methods: We analyzed and summarized the data on 520 disaster-related deaths in Minamisoma City, a municipality near the Fukushima Daiichi Nuclear Power Plant, focusing on the number of relocations. Herein, we describe the cases of three individuals over 80 years old, who died after eight or more relocations, which were certified as disaster-related deaths. Results: We discuss following three cases, which are (1) a female patient in her 90s who had a stroke and was completely disabled, (2) a female patient in her 80s whose cancer was detected later due to her failing to see her family doctor, and (3) a male patient in his 80s whose regular postoperative treatment was disrupted following cancer recurrence. Discussion: Our findings indicate that evacuation led to the worsening of chronic diseases and eventually to post-disaster death. Prolonged wide-area evacuation and repeated relocation likely interrupted the continuum of care and led to the failure of adequate care provision. To reduce the loss of human life, it is necessary to review the number of wide-area evacuations and relocations over the medium to long term after large-scale disasters, including nuclear disasters, which may occur in the future. Simultaneously, it is important to establish a medical system at the evacuation site so that disaster victims can continue to receive medical care even after evacuation or relocation.